Narrowband Ultraviolet B emission from gadolinium and praseodymium co-activated calcium phosphate phosphors for phototherapy lamps - Mokoena, Puseletso Pricilla (University of the Free State, 2014)
Different phases of calcium phosphates co-doped with gadolinium and praseodymium were prepared by co-precipitation, urea combustion, citrate-gel combustion and microwave-assisted methods. Ca5(PO4)3OH:Gd3+,Pr3+ phosphors were prepared by the co-precipitation and citrate-gel methods, and were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Scanning electron microscopy (SEM), High resolution transmission electron microscopy (HRTEM), Energy dispersive x-ray spectrometer (EDS) and photoluminescence (PL) spectroscopy. The XRD pattern was consistent with the hexagonal phase of Ca5(PO4)3OH referenced in JCPDS Card Number 73-0293. The XPS data indicated that Ca2+ occupied two different lattice sites referred to as Ca1 and Ca2. The P5+ is surrounded by O2- ions in the tetrahedral arrangements. Each tetrahedron contains oxygen atoms designated as O1, O2, and O3. The particle morphology was analyzed using SEM and HRTEM. SEM shows that the powder was composed of an agglomeration of irregular particles. HRTEM revealed faceted edges forming a hexagonal shape. PL data exhibited a narrowband emission located at 313 nm, which is associated with the 6P7/2→8S7/2 transition of the Gd3+ ion. This emission is classified as ultraviolet B (UVB) and it is suitable for use in phototherapy lamps to treat various skin diseases. The PL intensity of the 313 nm emission was enhanced considerably by Pr3+ co-doping. The crystallographic structure of Ca5(PO4)3OH:Gd3+,Pr3+ and possible mechanism of energy transfer from Pr3+ to Gd3+ are discussed. Ca5(PO4)3OH:Gd3+,Pr3+ phosphor exhibited a single thermoluminescence peak between 339-363 K. The peak shifted towards high temperature with an increase in dose. The shift shows that the trap system is more complicated than a single trap obeying first order kinetics. The calculated activation energy (EA) was found to be 0.91 eV when the using initial rise method. The activation energy values were further calculated using the peak shape method. The calculated activation energies for , and , were 0.75, 1.03, and 0.42 eV respectively. There was a peak shifting to higher temperatures with an increase in heating rate which is attributed to recombination that is slowing down due to electron-phonon interactions. The peak intensity increased with an increase in heating rate from 0.6 to 2.0 °C.s-1 and started to decrease from 3.0 to 5.0 °C.s-1, the decrease maybe due to thermal quenching as the peak shift to higher temperatures. The calculated activation energy by heating rate method was found to be 0.60 eV. This value is comparable to other calculated values of activation energies by various methods mentioned above. Ca3(PO4)2:Gd3+,Pr3+ phosphors with different concentrations of Gd3+ and Pr3+ were successfully prepared by urea combustion process using metal nitrates as precursors and urea as fuel and also by the microwave assisted method. XRD exhibited a rhombohedral phase of Ca3(PO4)2 referenced in JCPDS Card No. 70-2065. The PL excitation spectra of Ca3(PO4)2:Gd3+ and Ca3(PO4)2:Pr3+exhibited peaks at 220-280 nm and 300-490 nm associated with the f-f transitions of Gd3+and Pr3+ respectively. The UVB emission resulting from the 6P7/2→8S7/2 transition of Gd3+ was observed at 313 nm when the Ca3(PO4)2:Gd3+ phosphor was excited at a wavelength of 274 nm using a monochromatized xenon lamp. Upon Pr3+ co-doping, the excitation peaks due to Gd3+ and Pr3+ f-f transitions were suppressed and an intense broad excitation peak ascribed to the 4f4f5d transitions of Pr3+ was observed at 227 nm. The peak intensity of the UVB emission at 313 nm was shown to improve considerably when the Gd3+ and Pr3+ co-doped systems were excited at the wavelength of 227 nm suggesting that the Pr3+ is a good sensitizer of the 313 nm narrow line UVB emission from Gd3+.
Dissertation (M.Sc. (Physics))--University of the Free State, 2014
Keywords: Biocompatible material; Ultraviolet radiation; Phototherapy; Skin -- Diseases -- Phototherapy; Calcium phosphate; Energy transfer; UV radiation; Phototherapy lamps